Polymer of Intrinsic Microporosity (PIM-1) Membranes Treated with Supercritical CO2 - Colin A. Scholes; Shinji Kanehashi (Membranes, 2019)
Polymers of intrinsic microporosity (PIMs) are a promising membrane material for gas separation, because of their high free volume and micro-cavity size distribution. This is countered by PIMs-based membranes being highly susceptible to physical aging, which dramatically reduces their permselectivity over extended periods of time. Supercritical carbon dioxide is known to plasticize and partially solubilise polymers, altering the underlying membrane morphology, and hence impacting the gas separation properties. This investigation reports on the change in PIM-1 membranes after being exposed to supercritical CO2 for two- and eight-hour intervals, followed by two depressurization protocols, a rapid depressurization and a slow depressurization. The exposure times enables the impact contact time with supercritical CO2 has on the membrane morphology to be investigated, as well as the subsequent depressurization event. The density of the post supercritical CO2 exposed membranes, irrespective of exposure time and depressurization, were greater than the untreated membrane. This indicated that supercritical CO2 had solubilised the polymer chain, enabling PIM-1 to rearrange and contract the free volume micro-cavities present. As a consequence, the permeabilities of He, CH4, O2 and CO2 were all reduced for the supercritical CO2-treated membranes compared to the original membrane, while N2 permeability remained unchanged. Importantly, the physical aging properties of the supercritical CO2-treated membranes altered, with only minor reductions in N2, CH4 and O2 permeabilities observed over extended periods of time. In contrast, He and CO2 permeabilities experienced similar physical aging in the supercritical treated membranes to that of the original membrane. This was interpreted as the supercritical CO2 treatment enabling micro-cavity contraction to favour the smaller CO2 molecule, due to size exclusion of the larger N2, CH4 and O2 molecules. Therefore, physical aging of the treated membranes only had minor impact on N2, CH4 and O2 permeability; while the smaller He and CO2 gases experience greater permeability loss. This result implies that supercritical CO2 exposure has potential to limit physical aging performance loss in PIM-1 based membranes for O2/N2 separation.